Remediation and mediamachia in ekphrases - Milián, Orsolya (Primerjalna književnost, 2019)
Remediation as conceived by Jay David Bolter and Richard Grusin designates a kind of intermedial relationship in which various media may refashion or appropriate, pay homage to or rival one another. Taking as example the literary form of ekphrasis, understood in its narrower sense as the literary description of a visual work of art, this article examines ekphrasis as a technique of remediation. Following Bolter and Grusin's understanding of remediation and W. J. T. Mitchell's analysis of the text-image dialectic, this article aims at outlining the traits of the paragonal struggle (that is mediamachia) between word/text and image in The Parable of the Blind by William Carlos Williams and Der Blindensturz by Gisbert Kranz. Firstly, it establishes a theoretical framework within which the differentiation of ekphrasis as a strategy of verbal hypermediacy becomes possible. Secondly, it presents a comparative analysis of the above mentioned poems, showing that while Williams's poem effaces the visual Brueghel's The Parable of the Blind keeping its traits in verbal allusions only, and in a sense repressing the image in order to create its own verbal "self-portrait", Kranz's poem adds another stratum to the mediatization of Brueghel's painting through verbal description, namely the typographic image of the verbal text which exhibits the "skeleton" of the original pictorial composition as well. Thus, Kranz's poem might be considered as a form of multiplied hypermediacy. As opposed to Williams's more conventional ekphrasis, Kranz also rearranges the traditional word-image hierarchy of ekphrases (that tend to give supremacy to words) in that it vindicates a more "democratic" or balanced relation between the verbal and the visual medium.
Keywords: Bruegel, Pieter; ekfraza; intermedialnost; književnost in likovna umetnost; Kranz, Gisbert; opis podob; poezija; Williams, William Carlos